Aplicação de água de reúso tratada no cultivo de alface (Lactuca sativa L.) - Urbano, Vanessa Ribeiro (2013)
The concern in developing strategies to solve the water scarcity problem is growing and actual. As a big consumer of the available fresh water, agriculture is the activity with the biggest potential for applying of water reuse. This study set up in CCA/UFSCar evaluated, on laboratory conditions, the physical and chemical properties of a soil irrigated with treated wastewater after the application of a water sheet corresponding to five cycles of lettuce s growth (Lactuca sativa, L.) and in a greenhouse, evaluated the sanitary characteristics and mass of the Elisa type lettuce and the physical, chemical and microbiological characteristics of the soil after the cultivation with treated wastewater, comes from the wastewater treatment plant from the university. In the laboratory experiment, eighteen undisturbed soil samples were coupled in a constant head permeameter and received a water sheet corresponding to five cycles of lettuce s growth, 0.58, 1.16, 1.74, 2.32 and 2.9 L of water for each cycle. The soil samples were distributed in five groups that received treated wastewater and one control group that received distilled water. Soil samples were collected to analyze the granulometry, saturated hydraulic conductivity (ksat), exchangeable sodium percentage (ESP) and soil fertility. Treated wastewater and distilled water leached samples were collected to analyze the electrical conductivity, sodium adsorption ratio (SAR), turbidity, pH, sodium, potassium, magnesium, phosphorus, calcium and nitrate. In a greenhouse, two cycles of Elisa lettuce were cultivated with two treatments (treated wastewater and supply water) with four repetitions. After the harvest of the lettuce, soil samples were collected to analyze granulometry, density, ksat, and soil fertility, total coliforms, Escherichia coli and heterotrophic. The harvested lettuces were analyzed for total coliforms, Escherichia coli and chemical analysis of plant tissue. In laboratory, there was an increase of ESP and the concentration of phosphorus and sodium on soil after the application of the water sheet. There wasn t significant difference on the physical properties of soil, turbidity and SAR. In a greenhouse, there wasn t significant difference between the treatments on nutrients absorption of lettuces cultivated, but the weight of lettuces irrigated with wastewater was 100% greater than the lettuces irrigated with supply water on the second cycle. It was not detected the presence of Esherichia coli on the cultivated lettuces, but there was total coliforms contamination, that presents a risk of contamination to the consumer. The irrigation with treated wastewater increased the nutrients on soil and the SAR indicated a soil salinization risk. The treated wastewater does not cause damage on the physical properties of soil.